Geochemistry of the late Archean Banting Group, Yellowknife greenstone belt, Slave Province, Canada: simultaneous melting of the upper mantle and juvenile mafic crust - Cousens, Brian; Facey, Kathy; Falck, Hendrik (Canadian Journal of Earth Sciences, 2002)
This study investigates the geochemistry and tectonic setting of the 2.66 Ga Banting Group, the younger sequence of volcanic rocks in the Yellowknife greenstone belt, and its relationship to older tholeiitic volcanic rocks of the 2.722.70 Ga Kam Group. The Banting Group includes a much higher proportion of felsic volcanic and volcaniclastic rocks than the Kam Group, but mafic to intermediate volcanic rocks are common. Banting basalts are tholeiitic and are melts of Archean depleted upper mantle, as are basalts of the Kam Group. In contrast, Banting dacites and rhyolites have much lower heavy rare earth element abundances and generally have higher initial 143 Nd/ 144 Nd than Kam felsic rocks. The chemistry of the felsic rocks provides a geochemical signature to distinguish rocks of Kam versus Banting age where complex structures have obscured the stratigraphy. Whereas Kam felsic rocks evolved from mafic parents by assimilation fractional crystallization processes, Banting felsic rocks have compositions similar to Archean tonalitetrondhjemitedacite suites, as well as modern adakites, and appear to be melts of juvenile, garnet-bearing, hydrated mafic crust, possibly underplated Kam basalts. The nearby 2.66 Ga felsic complex at Clan Lake mimics the geochemical systematics of the Banting Group, and thus Banting-like rocks may reflect a regional crustal melting event at this time.